Prognostic value of Osteopontin (SPP1) in colorectal carcinoma requires a personalized molecular approach. Issue 9 (September 2019) - Assidi, Mourad; Gomaa, Wafaey; Jafri, Mohammad; Hanbazazh, Mehenaz; Al-Ahwal, Mahmoud; Pushparaj, Peter; Al-Harbi, Asia; Al-Qahtani, Mohammed; Buhmeida, Abdelbaset; Al-Maghrabi, Jaudah
Stratification of colorectal cancer for better management and tangible clinical outcomes is lacking in clinical practice. To reach this goal, the identification of reliable biomarker(s) is a prerequisite to deliver personalized colorectal cancer theranostics. Osteopontin (SPP1) is a key extracellular matrix protein involved in several pathophysiological processes including cancer progression and metastasis. However, the exact molecular mechanisms regulating its expression, localization, and molecular functions in cancer are still poorly understood. This study was designed to investigate the SPP1 expression profiles in Saudi colorectal cancer patients, and to assess its prognostic value. Hundred thirty-four (134) archival paraffin blocks of colorectal cancer were collected from King Abdulaziz University Hospital, Saudi Arabia. Tissue microarrays were constructed, and automated immunohistochemistry was performed to evaluate SPP1 protein expression patterns in colorectal cancer. About 20% and 23% of our colorectal cancer samples showed high SPP1 cytoplasmic and nuclear expression patterns, respectively. Cytoplasmic SPP1 did not correlate with age, gender, tumor size, and location. However, significant correlations were observed with tumor grade ( p  = 0.008), tumor invasion ( p  = 0.01), and distant metastasis ( p  = 0.04). Kaplan–Meier survival analysis showed a significantly lower recurrence rate in patients with higher SPP1 cytoplasmic expression ( p  = 0.05). At multivariate analysis, high SPP1 cytoplasmic expression was an independent favorable prognostic marker ( p  = 0.02). However, nuclear SPP1 expression did not show any prognostic value ( p  = 0.712). Our results showed a particular SPP1 prognostic relevance that is not in line with most colorectal cancer previous studies that may be attributed to the molecular pathophysiology of our colorectal cancer cohort. Saudi Arabia has both specific genomic makeup and particular environment that could lead to distinctive molecular roots of cancer. SPP1 has several isoforms, tissue localizations and molecular functions, signaling pathways, and downstream molecular functions. Therefore, a more individualized approach for CRC studies and particularly SPP1 prognosis outcomes' assessment is highly recommended toward precision oncology.